Screening of native entomopathogenic nematodes against semi-looper (Synegia sp.) infesting black pepper (Piper nigrum L.) - Rajkumar, Rashid Pervez, S.J. Eapen (Journal of Plantation Crops, 2017)
Several insect pests damage and caused economic losses to black pepper (Piper nigrum L.). Among them semi-looper (Synegia sp.) is an important pest especially in younger vines of black pepper. Pesticides are currently being used to manage this pest leading to environmental and health concerns. Screening for virulence of eight native entomopathogenic nematodes were tested against the semi-looper (SL). The suitability of this insect for multiplying EPNs, attachment to and penetration into host was also studied. Among test EPNs, Heterorhabditis sp. (IISR-EPN 01), Steinernema sp. (IISR-EPN 02) and O. gingeri (IISR-EPN 07) were more virulent to semi-looper as they caused 100 per cent mortality to SL within 72 h. Maximum number of infective juveniles (IJs) attached into larva at 6 and 12 h post exposure. Maximum number of Steinernema sp. (IISR-EPN 02) IJs penetrated into larva (12.5 IJs per larva), followed by Heterorhabditis sp. (IISR-EPN 01) (8.7 IJs per larva) and only 5.9 IJs per larva of O. gingeri (IISR-EPN 07) penetrated into the test insect body. Maximum multiplication of IJs was observed with O. gingeri (IISR-EPN 07), which yielded 9,324 IJs per larva within 15 days, followed by Oscheius sp. (IISR-EPN 04) (8,638 IJs per larva) and Oscheius sp. (IISR-EPN 08) (8,236 IJs per larva). The infectivity of EPNs against semi-looper (Synegia sp.) is being reported for the first time which opens up a new vista in eco-friendly insect pest management in black pepper.